2002
DOI: 10.1186/1475-925x-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Temperature measurement on neurological pulse generators during MR scans

Abstract: According to manufacturers of both magnetic resonance imaging (MRI) machines, and implantable neurological pulse generators (IPGs), MRI is contraindicated for patients with IPGs. A major argument for this restriction is the risk to induce heat in the leads due to the electromagnetic field, which could be dangerous for the surrounding brain parenchyma. The temperature change on the surface of the case of an ITREL-III (Medtronic Inc., Minneapolis, MN) and the lead tip during MRI was determined. An anatomical rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Currently, it is considered safe to scan patients with implanted DBS systems only if specific guidelines are observed. 14,33 Recommended exposures for RF energy include SAR < 4.0 W/kg whole body for 15 minutes, 3.0 W/ kg averaged over the head for 10 minutes, 8.0 W/kg in any gram of tissue in the head or torso for 15 minutes, or 12.0 W/kg in any gram of tissue in the extremities for 15 minutes. In December 2015, the Activa portfolio (Medtronic, Inc.) of DBS neurostimulators received Food and Drug Administration approval for full-body MRI under specific conditions of use.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is considered safe to scan patients with implanted DBS systems only if specific guidelines are observed. 14,33 Recommended exposures for RF energy include SAR < 4.0 W/kg whole body for 15 minutes, 3.0 W/ kg averaged over the head for 10 minutes, 8.0 W/kg in any gram of tissue in the head or torso for 15 minutes, or 12.0 W/kg in any gram of tissue in the extremities for 15 minutes. In December 2015, the Activa portfolio (Medtronic, Inc.) of DBS neurostimulators received Food and Drug Administration approval for full-body MRI under specific conditions of use.…”
Section: Discussionmentioning
confidence: 99%
“…Active medical devices such as pacemakers and implantable neurological pulse generators (IPGs) have been studied extensively since these devices are implanted inside vital parts of the human body, such as heart muscle or brain. Kainz et al [7] reported a maximum of 2.1°C temperature increases at the lead tip for neurological pulse generators. However, some other studies found much higher temperature rise which could be harmful to humans.…”
Section: Introductionmentioning
confidence: 99%
“…The MoTLiM may have applications beyond the heating of implants during MRI, such as in cell phone implant interactions. There are studies that have analyzed SAR gain in the presence of a deep brain stimulator 22 during the use of cell phones. The MoTLiM may also be used to calculate induced currents on these implants when they interact with cell phones.…”
Section: Discussionmentioning
confidence: 99%